Power handling of a liquid-metal based CPS structure under high steady-state heat and particle fluxes. (August 2017) - Morgan, T.W.; Vertkov, A.; Bystrov, K.; Lyublinski, I.; Genuit, J.W.; Mazzitelli, G.
Highlights: Plasma exposure of a Sn-filled CPS target up to 18 MW m-2 showed good performance. No damage to mesh nor loss of wetting was observed. No droplets were produced in agreement with K-H and R-T stability analysis. Analysis of the performance of the target determined the mesh thermal properties. Finite element modelling indicates Sn-CPS armour could sustain 20 MW m-2 in DEMO. Abstract: Liquid metal infused capillary porous structures (CPSs) are considered as a potential divertor solution for DEMO due to their potential power handling capability and resilience to long term damage. In this work the power handling and performance of such Sn-based CPS systems is assessed both experimentally and via modelling. A Sn-CPS target was exposed to heat fluxes of up to 18.1 MW m −2 in He plasma in the Pilot-PSI linear device. Post-mortem the target showed no damage to nor any surface exposure of the underlying W-CPS felt. The small pore size (∼40 µm) employed resulted in no droplet formation from the target in agreement with calculated Rayleigh-Taylor and Kelvin-Helmoholtz instability thresholds. The temperature response of the Sn-target was used to determine the thermal conductivity of the mixed Sn-CPS material using COMSOL modelling. These values were then used via further finite element analysis to extrapolate to DEMO relevant monoblock designs and estimate the maximum power handling achievable based on estimated temperature windows for all component elements of the design. For an optimized design a heat-load of up to 20 MW m −2 may be received while the use of CPS also offers other potential design advantages such as the removal of interlayer requirements.